Discourse Dynamics and Cultural Representation in Indonesian Cinema: A Case Study of Sayap-Sayap Patah Dua - Qani'ah, Binti (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study investigates the discourse dynamics and cultural representations conveyed through Indonesian cinema, with a specific focus on the film Sayap-Sayap Patah Dua. The primary research problem centers on understanding how cinematic discourses employ visual and linguistic strategies to reflect, construct, and challenge socio-cultural realities in contemporary Indonesia. The objective of this research is to analyze the underlying discourse mechanisms that reveal social tensions, cultural identities, and power relations within the film. Employing a qualitative critical discourse analysis (CDA) approach, the study systematically examines visual symbolism, dialogue patterns, and narrative structures to uncover the layered meanings embedded in the cinematic text. The analysis identifies recurring metaphors such as “wings” symbolizing freedom and repression, alongside language patterns that depict social hierarchies and cultural tensions. The results demonstrate that the film not only portrays societal struggles but also actively participates in shaping discursive debates around authority, individual agency, and cultural identity in Indonesia. Such findings contribute to the broader understanding of film as a potent medium for cultural discourse and social critique. This research underscores the importance of analyzing cinematic discourse to appreciate its role in cultural representation and societal transformation. The study also highlights the significance of visual and linguistic strategies in shaping perceptions of social realities through cinema. Limitations include the focus on a single film, suggesting future research avenues such as comparative studies across multiple cinematic texts or audience reception analysis to deepen insights into cinema’s influence on social discourse.